The Significance of Herzberg and Taylor for the Gig Economy of China: Evaluating Gigger Incentives for Meituan and Ele.me - Boidurjo Rick Mukhopadhyay; Chris R. Chatwin (Global Labor Organization (GLO), 2021)
This article investigates the motivation of contingent workers in the gig economy of China, particularly focusing on the two Mobile Food Delivery Aggregators (MFDA) - Meituan and Ele.me that controls over 80% of the food delivery market in China. The convenience of one 'super-app' on phone, offered by each of these companies, allows users to order a diversified range of products and services starting from food, clothing to travel booking and ride-hailing. Online food ordering, however, tops the chart of online orders and this creates millions of food delivery rider jobs/gigs in mainland China. This paper draws key insights from the employee motivation theories by Herzberg and Taylor which underpins the findings and thematic discussion of this qualitative paper. While it is important to recognise that the usage growth of these MFDAs and consequently new gig creation is exponentially growing, the implications of this research would inform these online platform-based companies how to better design motivational factors or incentives to boost their employee satisfaction, engagement and levels of commitments in the colossal Gig economy of mainland China.
Keywords: D86; J41; L86; M51; M52; M54; M55; O30; 330; Gig Economy; Contingent Workforce Management; Employee Engagement; Employee Motivation; Employee Retention; Scientific Management Theory; Two-Factor Theory; Collaborative Consumption; China; Mobile Food Delivery Aggregators (MFDA); Meituan-Dianping; Ele.me; Platforms